Earth Watch: Feeding the World - Walpole, Brenda (Franklin Watts, 2000)
Earth Watch is an introduction to ecology and environmental science. It looks at the world around us, how it is changing, and how we can help to keep the balance of nature$1! =s
Keywords: Juvenile Non-Fiction / Agriculture